Keanekaragaman Jenis Tumbuhan Obat Di Wisata Alam Desa Kapopo Kabupaten Sigi Biromaru Provinsi Sulawesi Tengah - Korja, I Nengah; Lestari, Nur Indah (ForestSains, 2019)
A forest park is a nature conservation area for the purpose of collection of plants and / or non-originals, which are used for research, science, education supporting cultivation, culture, tourism and recreation. This research was conducted for 2 months, from July to September 2019 in the Kapopo forest Park, the great forest area, Ngatabaru, Sigi Biromaru District, Sigi Regency, Central Sulawsi Province. The study was conducted using a survey method by making a path by intentional sampling of the starting point based on the type of medicinal plant found. The results showed 17 species of medicinal plants found from 12 families. Diversity of medicinal plants at tree growth rates of 0.79. The pole level is 1.22. The stake rate is 0.21. At the level of seedlings and undergrowth obtained at 0,25. So the diversity of medicinal plants according to growth rates are generally classified as low to moderate.